Economic and administrative importance of the regulation of transport platforms public in Colombia (2020)
This essay on the economic and administrative importance of the regulation of platforms public transport in Colombia is developed initially on the study of shared economic growth levels and applicability to developing economies like Colombia, with its disruptive growth that you can evaluate and define in a specific market that has generated controversy in Colombia as is the transport of passengers, which seeks to examine advantages and disadvantages of this type of economy and seek to describe why no special treatment is given to an issue of great importance by the public administration, examining assumptions as why his arrival was not taken into account by the three state powers, or that has been its implementation and the causes of their welcome under three main assumptions as they are, the legal vacuum allowing what is not regulated or as an employment opportunity that impairs the social security systems of a developing country presents and lack of study and updating of economic models and regulatory successful on the guild taxi drivers in Colombia, which allowed greater acceptance by Uber to evaluate how the company has permeated such an important market, taking more than 2.3 million users and generate employment 88,000 people but also determining the negative factors mockery of the administrative system of the Colombian State supported in a conflict of interest by public authorities, to finish at or after 10 years of arrival if you can take into account and generate solutions bills to regulate the labor market.